Influential factors on urine EV DNA methylation detection and its diagnostic potential in prostate cancer - Ding, Ting; Diao, Yanjun; Zeng, Xianfei; Zhou, Lei; Wu, Guojun; Liu, Jiayun; Hao, Xiaoke (Frontiers in Genetics, 2024)
The value of Extracellular vesicles (EVs) diagnostic markers is widely recognized; however, current research on EV DNA remains limited. This study investigates the biological properties, preprocessing factors, and diagnostic potential of EV DNA. We found that DNA positive vesicles account for 23.3±6.7% of the urine total EV, with a large amount of DNA attached to the outsid. EV DNA fragments are large, there is no significant effect on uEV DNA when store urine less than 6h at 4℃ . In addition, the influence of different EV extraction methods on methylation detection is also minor. More importantly, RASSF1A methylation in urine total EV DNA can distinguish between PCa and BPH, with an AUC of 0.874. Our results suggest the potential of urine EV DNA as a novel marker for PCa diagnosis. This provides a new idea for the study of urinary tumor markers.